Non‐Viral Gene Delivery via Membrane‐Penetrating, Mannose‐Targeting Supramolecular Self‐Assembled Nanocomplexes - Lichen Yin; Ziyuan Song; Kyung Hoon Kim; Nan Zheng; Nathan P. Gabrielson; Jianjun Cheng (2013)
Supramolecular self-assembled nanocomplexes (SSANs) capable of mannose receptor-mediated endocytosis and permeable to cellular and endosomal membranes are developed via the assembly of multiple rationally designed, function-specific materials. As a unique non-viral gene delivery vector, SSANs outperform commercial transfection reagents, including LPF2000, PEI, and jetPEI, by up to 2 orders of magnitude.